2008
DOI: 10.1007/s12237-008-9054-7
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Organic Carbon in Todos Santos Bay, Baja California, Mexico

Abstract: Sediment grain size and organic carbon (OC) data collected over the past 50 years, together with δ 13 C values of OC in recently collected samples, were analyzed to improve understanding of sediment OC distribution and abundance in Todos Santos Bay. Sediments in the submarine canyon at the mouth of the bay and in quiet-water locations along the shore are fine grained, high in OC, and have generally low δ 13 C values; sediments in high-energy environments are low in OC and have high δ 13 C values. A bivariate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…2). The grain-size distribution is very similar to that reported by Smith et al (2008), where the grain-size is dominated by silt. The spatial trend of grain size indicates a zone of deposition of fine material in the central area of the bay (a depocenter), consistent with the convergent surface current system, longshore transport and sediment transport in the bay (Sanchez et al, 2009).…”
Section: Grain-size Trendssupporting
confidence: 86%
“…2). The grain-size distribution is very similar to that reported by Smith et al (2008), where the grain-size is dominated by silt. The spatial trend of grain size indicates a zone of deposition of fine material in the central area of the bay (a depocenter), consistent with the convergent surface current system, longshore transport and sediment transport in the bay (Sanchez et al, 2009).…”
Section: Grain-size Trendssupporting
confidence: 86%
“…The surface water circulation inside TSB is associated with the intensity and direction of the winds. The prevailing northwesterly winds (annual mean intensity of 4.8 m s −1 ; Castro and Martínez, 2010), present primarily during the spring and summer, drive water into the bay from the northern entrance (Smith et al, 2008). This flow of water, in The bay was divided into three main areas: a) the inner (stations 1-3), b) and the outer bay (stations 4-5), and c) the upwelling zone (UZ; station 6) located outside of the bay.…”
Section: Description Of the Study Sitementioning
confidence: 99%
“…The distribution and sources of the OM has been extensively studied in transitional systems influenced by rivers and extreme runoffs (e.g., Hu et al, 2006;Niggemann et al, 2007;Cowie et al, 2009;Smith et al, 2008;Walinsky et al, 2009;Baumgart et al, 2010), which contrasts with the arid regions that are characterized by low terrigenous input and coastal upwelling, overlying an oxygen minimum zone. However, the contributions from the mangroves in the lagoon system of Bahia Magdalena-Almejas could be a significant source of OM to the margin of the southwestern Baja California Peninsula.…”
Section: Discussionmentioning
confidence: 99%
“…The average value for d 13 C surface sediments was -22‰, indicating a 23% contribution from the scarce local desert vegetation or the mangroves. Smith et al (2008) suggested that the maximum terrigenous TOC content of sediments in Bahia Todos Santos is <50% with an average near 30%, where the OM contribution of terrigenous origin increases in the offshore direction. However, the sedimentation rate might alter the estimated average terrigenous contents, but these authors suggest that this effect would be relatively small.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation